HUBUNGAN TEHNIK ICE BREAKING DENGAN TINGKAT KEJENUHAN BELAJAR DALAM PROSES PEMBELAJARAN TEMATIK - Eva Yuliyanti; Iffah Mukhlisah; Indah Nurhidayati (Al'Ulum Jurnal Pendidikan Islam, 2021)
This research was conducted to determine the relationship between ice breaking techniques and the level of learning saturation in the thematic learning process of class III MI Nurul Huda Polokarto Packaging in 2021/2022. The subject of this study was a grade III student of MI Nurul Huda. This research uses a quantitative approach with a correlational type. The data collection method is in the form of a questionnaire or questionnaire. Population and study sample of 17 students, data analysis techniques using moment product correlation. The results of this study show that there is a relationship between ice breaking techniques and the level of learning saturation as evidenced by obtaining an rxy value of -0.488 in the medium category with a sig of 0.047, namely < 0.05 and rhitung > r table = -0.488 > 0.482 meaning that there is a significant negative relationship between ice breaking techniques and student learning saturation levels so that H0 is rejected and H1 is accepted. This shows that "there is a relationship between ice breaking techniques and the level of learning saturation of grade III MI nurul Huda Polokarto packaging students in 2021/2022".